Carotid wall structure during and after 6 months of spaceflight - Arbeille, Philippe; Zuj, Kathryn; Greaves, Danielle; Hughson, Richard (Frontiers in Physiology, 2025)
PurposeLong-duration spaceflight has been shown to result in vascular adaptation. However, little is known about the recovery of these parameters after the flight. The purpose of our study was to assess the common carotid (CC) artery wall properties before, during, and after 6 months of spaceflight on the International Space Station (ISS).MethodsCC artery wall properties were assessed using ultrasound measures of the intima media thickness (IMT) and the evaluation of the radiofrequency signal to determine the index of reflectivity (IR) for the posterior wall, posterior intima, and neck muscle. Data were collected from ten astronauts preflight (PRE), on flight day 150 (FD150), and 4 days (R+4) and 6 months (R+6 m) postflight.ResultsIMT increased from PRE (0.56 ± 0.09 mm) to FD150 (0.65 ± 0.11 mm) and R+4 (0.65 ± 0.08 mm), and returned to PRE levels on R+6 m (0.57 ± 0.12 mm). Posterior wall IR also increased from PRE (63% ± 5.5%) to FD150 (78% ± 7.8%) and R+4 (86% ± 4.4%), and returned to PRE levels on R+6 m (60% ± 23%). In contrast, both intima IR and neck muscle IR increased slightly during spaceflight but returned to preflight levels on R+4.ConclusionChanges in CC posterior wall IMT and IR that persisted at R+4 but normalized at R+6 m suggest structural or content modifications of the vessel wall. In contrast, the early recovery of neck muscle and posterior wall intima IR at R+4 suggests a transient process that is possibly related to microgravity-induced fluid shifts.